A pilot open-label study of aldose reductase inhibition with AT-001 (caficrestat) in patients hospitalized for COVID-19 infection: Results from a registry-based matched-control analysis. Issue 6 (November 2021) - Gaztanaga, Juan; Ramasamy, Ravichandran; Schmidt, Ann Marie; Fishman, Glenn; Schendelman, Shoshana; Thangavelu, Karthinathan; Perfetti, Riccardo; Katz, Stuart D.
Abstract: Background and aims: Cardiometabolic disease may confer increased risk of adverse outcomes in COVID-19 patients by activation of the aldose reductase pathway. We hypothesized that aldose reductase inhibition with AT-001 might reduce viral inflammation and risk of adverse outcomes in diabetic patients with COVID-19. Methods: We conducted an open-label prospective phase 2 clinical trial to assess safety, tolerability and efficacy of AT-001 in patients hospitalized with COVID-19 infection, history of diabetes mellitus and chronic heart disease. Eligible participants were prospectively enrolled and treated with AT-001 1500 mg BID for up to 14 days. Safety, tolerability, survival and length of hospital stay (LOS) were collected from the electronic medical record and compared with data from two matched control groups (MC1 and MC2) selected from a deidentified registry of COVID-19 patients at the same institution. Results: AT-001 was safe and well tolerated in the 10 participants who received the study drug. In-hospital mortality observed in the AT-001 group was 20% vs. 31% in MC1 and 27% in MC2. Mean LOS observed in the AT-001 group was 5 days vs. 10 days in MC1 and 25 days in MC2. Conclusions: In hospitalized patients with COVID-19 and co-morbid diabetes mellitus and heart disease, treatment with AT-001 was safe and well tolerated. Exposure to AT-001 was associated with a trend of reduced mortality and shortened LOS. While the observed trend did not reach statistical significance, the present study provides the rationale for investigating potential benefit of AT-001 in COVID 19 affected patients in future studies. Highlights: Treatment with AT-001 decreases length of hospital stay in subjects with diabetes mellitus (DM) hospitalized for COVID-19. Subjects with DM hospitalized for COVID-19 experience a trend toward decreased mortality after being treated with AT-001. Treatment with AT-001 is safe and well-tolerated in subjects with DM and history of heart disease hospitalized for COVID-19.